2004
DOI: 10.1086/420744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Hepatitis B Virus (HBV) Infection on Outcomes of Patients Infected with HIV in an Area Where HBV Infection Is Hyperendemic

Abstract: Between June 1994 and February 2003, a total of 111 human immunodeficiency virus (HIV)-infected patients with chronic hepatitis B virus (HBV) coinfection and 387 HIV-infected patients without HBV or hepatitis C virus coinfection were prospectively observed to assess the impact of HBV infection on outcomes of HIV-infected patients. After a median duration of observation of 25 months, coinfected patients were more likely to develop hepatitis (adjusted hazard ratio [AHR], 2.54; 95% confidence interval [CI], 1.69-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
5
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 32 publications
9
57
5
1
Order By: Relevance
“…Regarding this point, our study is in agreement with a recent data from Taiwan that showed coinfected HIV patients with HBV were more likely to develop new opportunistic illnesses [43] . This significant association might be due to the fact that opportunistic infections may cause wounds on the surface of the body which might increase the probability of HBV transmission and infect the patients.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding this point, our study is in agreement with a recent data from Taiwan that showed coinfected HIV patients with HBV were more likely to develop new opportunistic illnesses [43] . This significant association might be due to the fact that opportunistic infections may cause wounds on the surface of the body which might increase the probability of HBV transmission and infect the patients.…”
Section: Discussionsupporting
confidence: 93%
“…Coinfection with HBV has been shown to increase the risk of acute hepatitis, hepatic decompensation, liver-related mortality, and virological failure in HIV-infected patients receiving highly active antiretroviral therapy (HAART) (8,26,33). For patients with HIV infection, clinical studies of the impact of HDV infection on patients with HBV and HIV coinfection were limited and yielded inconsistent results before the introduction of HAART (2,11,21,24).…”
mentioning
confidence: 99%
“…Several studies have shown that chronic HBV infection significantly increased liver-related mortality in HIV-1-infected patients but did not have a direct impact on progression to AIDS or on viral and immunological responses to ART. [24][25][26] However, studies from Taiwan found that individuals with chronic hepatitis B were less likely to achieve HIV RNA suppression at 4 and 24 months after initiation of ART. 26,27 Overall, it is still debated whether HBV co-infection might negatively affect the efficacy of antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%